Determination of thermal-mechanical properties of concrete - Delpak, Ramiz; Gailius, Albinas; Žukauskas, Dangyras (Journal of Civil Engineering and Management, 2002)
The aim of this investigation was to find the relationship between different percentage of damage and thermal conductivity of concrete. The influence of different damage on thermal conductivity of concrete was determined. The method with insulation (ordinary method) based on the temperature difference measurement between two surfaces of specimen, when one of the surfaces is heated, was used for thermal conductivity measurement. Three specimens for every percentage of damage were used for each measurement of thermal conductivity. After this research one conclusion can be made definitely: influence of different percentage of damage on thermal conductivity of concrete.Frist Published Online: 30 Jul 2012